2013
DOI: 10.1523/jneurosci.2532-12.2013
|View full text |Cite|
|
Sign up to set email alerts
|

Segregated Encoding of Reward–Identity and Stimulus–Reward Associations in Human Orbitofrontal Cortex

Abstract: A dominant focus in studies of learning and decision-making is the neural coding of scalar reward value. This emphasis ignores the fact that choices are strongly shaped by a rich representation of potential rewards. Here, using fMRI adaptation, we demonstrate that responses in the human orbitofrontal cortex (OFC) encode a representation of the specific type of food reward predicted by a visual cue. By controlling for value across rewards and by linking each reward with two distinct stimuli, we could test for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
139
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 54 publications
14
139
1
Order By: Relevance
“…Such a correspondence is consistent with this region being concerned with the mediation of behavioral change as a result of a general role in learning stimulus-reward associations (55,60,62). However, we were unable to match the more anterior human lOFC region linked to ambiguity (Fig.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…Such a correspondence is consistent with this region being concerned with the mediation of behavioral change as a result of a general role in learning stimulus-reward associations (55,60,62). However, we were unable to match the more anterior human lOFC region linked to ambiguity (Fig.…”
Section: Resultssupporting
confidence: 66%
“…For example, positive outcomes might lead to behavioral changes in learning situations. Consistent with this idea, some recent studies have suggested that the same lOFC region previously highlighted as responsive to punishers (33,56) has a more general role in credit assignment and the linking of stimuli to reward outcomes (55,60) (Fig. 5A).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations